Kinerja Keuangan Pemerintah Daerah di Provinsi Aceh Sebelum dan Saat Pandemi COVID-19 - Najla, Muti; Fahlevi, Heru (Studi Akuntansi dan Keuangan Indonesia, 2023)
This study aimed to determine whether there were differences between the financial performance of local governments (districts/cities) in Aceh before and during the COVID-19 pandemic. Data was collected from financial reports and budgets of district and city governments in Aceh, Indonesia, in 2019 and 2020. This study found mixed findings using the Paired Sample T-test and Wilcoxon Signed Rank Test. The local government's financial independence and financial efficiency during the COVID-19 pandemic were higher than before the COVID-19 pandemic, while local tax contributions decreased following the COVID-19 pandemic. This study also found that local government financial activities, financial effectiveness, and government retribution contributions before and during the COVID-19 pandemic were statistically not different. This study suggests the need to improve local government's financial autonomy and sustainability as a transfer from the central government may decline significantly within a short period, for instance, during the financial crisis and pandemic.